1994
DOI: 10.1007/bf02816124
|View full text |Cite
|
Sign up to set email alerts
|

Altered GABAergic and glutamatergic transmission in audiogenic seizure-susceptible mice

Abstract: The C57BL/10 SPS/sps mouse mutant are audiogenic seizure-susceptible. The enzymatic activities of glutamate decarboxylase (GAD), GABA aminotransferase (GABA-T), alanine aminotransferase (ALA-T), aspartate aminotransferase (ASP-T), and glutamate dehydrogenase (GDH) of whole brain supernatant are significantly reduced in these epileptic mice. GABA uptake is decreased in cortex, midbrain, and pons medulla. Previous studies showed the presence of two sodium-dependent GLU uptake systems in normal (SPS/SP) mice. Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Inhibition of the enzyme probably results in decreased Glu synthesis. Our finding is in agreement with the finding of Cordero et al (24), who observed decreased GLDH activity in audiogenic seizure‐susceptible mice.…”
Section: Discussionsupporting
confidence: 94%
“…Inhibition of the enzyme probably results in decreased Glu synthesis. Our finding is in agreement with the finding of Cordero et al (24), who observed decreased GLDH activity in audiogenic seizure‐susceptible mice.…”
Section: Discussionsupporting
confidence: 94%
“…Each column represents mean ± SEM; n = 5 for each group. *Յ0.05, significantly different from intact, control group (24),. who observed decreased GLDH activity in audiogenic seizure-susceptible mice.…”
mentioning
confidence: 80%
“…Cerebral imbalance of the major regulatory antagonistic systems, i.e., decreased GABAergic activity associated with increased excitatory aminoacidergic pathways, has been found to play a key role in initiating audiogenic seizures (Engstrom and Woodbury, 1988;Faingold et al, 1992Wieraszko and Seyfried, 1993;Cordero et al, 1994;Terra and Garcia-Cairasco, 1994). Mechanisms for audiogenic susceptibility also include reduction of C a 2ϩ ATPase activity (Palayoor and Seyfried, 1984;Palayoor et al, 1986;Seyfried et al, 1986), cyclic AM P responsiveness (L udvig et al, 1985), and histaminergic and adrenergic neuronal efficiencies (Jobe et al, 1986;T uomisto et al, 1987), as well as enhancement of glutamate decarboxylase mRNA expression (Ribak et al, 1993), and, as an adaptive mechanism for defective anion transport, of carbonic anhydrase activity (Woodbury et al, 1984;Engstrom et al, 1986;Faingold et al, 1986;Yu et al, 1986).…”
mentioning
confidence: 99%